2016
DOI: 10.1017/s2045796015001067
|View full text |Cite
|
Sign up to set email alerts
|

The future of mental health care: peer-to-peer support and social media

Abstract: Aims People with serious mental illness are increasingly turning to popular social media, including Facebook, Twitter or YouTube, to share their illness experiences or seek advice from others with similar health conditions. This emerging form of unsolicited communication among self-forming online communities of patients and individuals with diverse health concerns is referred to as peer-to-peer support. We offer a perspective on how online peer-to-peer connections among people with serious mental illness could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
540
2
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(583 citation statements)
references
References 74 publications
26
540
2
15
Order By: Relevance
“…These networks may be particularly helpful for patients with ongoing illnesses, conditions, or disabilities 46 as well as for those identifying as lesbian, gay, bisexual, transgender, questioning, or intersex (LGBTQI) seeking helpful information or a welcoming community. Recent literature indicates that transgender teenagers who feel supported by their families have lower rates of depression and anxiety.…”
Section: How Can Social Media Be Used To Promote Improved Health?mentioning
confidence: 99%
“…These networks may be particularly helpful for patients with ongoing illnesses, conditions, or disabilities 46 as well as for those identifying as lesbian, gay, bisexual, transgender, questioning, or intersex (LGBTQI) seeking helpful information or a welcoming community. Recent literature indicates that transgender teenagers who feel supported by their families have lower rates of depression and anxiety.…”
Section: How Can Social Media Be Used To Promote Improved Health?mentioning
confidence: 99%
“…5 In 1 study, young adults described the benefits of seeking health information online and through social media, and recognized these channels as useful supplementary sources of information to health care visits. 6 Research also supports the use of social media to foster social inclusion among users who may feel excluded 7 or who are seeking a welcoming community: for example, those identifying as lesbian, gay, bisexual, transgender, questioning, or intersex.…”
Section: Benefi Ts Of Mediamentioning
confidence: 99%
“…Studies have found several positive benefits of using Facebook and other SNSs for those with mental illness, such as an increase in perceived social support [73,74], feelings of empowerment and hope [75], reduced feelings of isolation [74], and a decrease in depressive symptoms [75]. In addition, those seeking online support have reported a lower level of stigmatisation [76], and increased feelings of connectedness [77].…”
Section: Social Networking Sites and Mental Health Supportmentioning
confidence: 99%